PERSIAPAN SERTIFIKASI HALAL DAN IZIN EDAR SEBAGAI UPAYA PENINGKATAN MUTU PRODUK PANGAN DAN KAPASITAS SDM MENUJU UMKM PANGAN UNGGUL DI KELURAHAN MULYAHARJA, BOGOR - Ai Imas Faidoh Fatimah; Nurafi Razna Suhaima; Mrr Lukie Trianawati; Made Gayatri Anggarkasih; Andi Early Febrinda; Dewi Sarastani; Dwi Yuni Hastati; Rianti Dyah Hapsari; Neny Mariyani; M. Agung Zaim Adzkiya; Aulia Irhamni Fajri; Aliefya Siwi Handayani Meylani Awaliyah; Arya Rafly Maulana Sopyan; Farras Zahran Musyafa (Jurnal Abdi Insani, 2026)
Mulyaharja Village is one of the areas in Bogor City with numerous small and medium enterprises (SMEs) producing household-scale food products (Industri Rumah Tangga Pangan / IRTP), such as rengginang, chips, jipang cakes, candied fruits, dodol, and various other processed foods. However, most of this food SMEs have not yet obtained business legality in the form of halal certification and distribution permits. This condition requires attention, as business legality is an essential requirement to ensure product quality, safety, and halal integrity, while also enhancing business competitiveness in the market. This community service program aimed to improve SME entrepreneurs’ understanding of halal certification and distribution licensing as part of efforts to enhance product quality and strengthen business capacity. The activity consisted of several stages, including preparation through coordination and discussion, training implementation, evaluation, and follow-up planning. The initial discussion identified relevant topics to ensure that the activities met community needs. The training, attended by 25 food SME owners under the Mulyaharja Bangkit organization, covered materials on halal certification procedures, distribution licensing mechanisms, and evaluation. Participants showed high enthusiasm, and evaluation results indicated an increase in their understanding of halal certification and distribution licensing for food products. The follow-up plan includes mentoring selected SMEs that meet the required criteria and are willing to participate. This program is expected to encourage food SMEs to obtain business legality, ensuring that their products meet quality, safety, and halal standards while improving their competitiveness in the market.